Implementasi Pembelajaran STEM Berbasis Education for Sustainable Development pada Topik Energi Terbarukan untuk Meningkatkan Kemampuan Berpikir Sistem - Kurniawan, Teddy; Abdurrahman, Abdurrahman; Rosidin, Undang (Journal of Teaching and Learning Physics, 2024)
The purpose of this study was to identify differences in students' systems thinking skills between teaching using the STEM approach based on Education for Sustainable Development (ESD) and conventional teaching on renewable energy. The study was conducted at SMAN 1 Menggala and the samples used were from XI IPA 3 and XI IPA 5 students. The research design used was a non-equivalent control group design and the instrument used to obtain the outcome data is reasoned multiple choice test questions. Based on the results and discussion it is known that there are differences in students system thinking skills between lessons using the STEM approach based on Education for Sustainable Development (ESD) and conventional lessons on renewable energy. This study also found that STEM learning based on Education for Sustainable Development (ESD) is more effective for increasing students' systems thinking skills on renewable energy material.